Design and Validation of Horizontal Steam Retort with Capacity of 100 kg Presto milkfish Using Finite Element Method (FEM) - Nofrizal Fajar Satria Pratama; Saputro, Danang Dwi (Universitas Negeri Semarang, 2024)
Retorts are used in the food processing industry to sterilize packaged food products. Sterilization of presto milkfish using retort is done at 120℃ and 2 bar pressure. The retort is designed to work safely under these load conditions. This study aims to determine the safety quality of the horizontal steam retort design. Design validation is done by static analysis using finite element method (FEM) with Solidworks software. The retort design uses 18Cr-8Ni type 304 stainless steel material, with a sterilization load of 120℃ temperature, 2 bar pressure, and 100 kg of milkfish load. The analysis showed that the most considerable Von-Mises stress occurred on the torispherical head with a value of . The largest displacement occurs at the torispherical head of the retort door with a value of 1.078 mm. The retort design is concluded to be safe to use under sterilization load conditions with a safety factor value of 2.9.